Garum, Fish Blood Taboos in the Judaeo-Christian World and the Evolving Nature of Ancient Fish Sauce - Grainger, Sally (Studia Ceranea, 2024)
The consumption of a fermented fish sauce appears as a fundamental part of Roman and Greek cuisine at every level of society and, in terms of amphora distribution, it was popular and widely consumed in every region of the empire. In the late Roman period, the fish sauces that were available appear to have subtly evolved in ways that reflect different attitudes to the consumption of fish blood. Sauces fermented using indigenous digestive enzymes from the viscera are in some instances rejected and replaced with the already familiar eviscerated and aged saltfish brines. These changes, though difficult to discern, may in part be related to the Judaeo-Christian prohibition on the consumption of blood which, though normally associated with meat, can also be understood to relate to fish blood. These differing attitudes towards fish sauce in relation to blood are to be found in orthodox Jewish and Christian communities in Palestine, Syria and Cyprus. In the late republic/early empire there appears to be three types of sauce and immense differences in quality depending on the species of fish employed, presence and absence of blood and viscera, salinity and the duration of fermentation. Under the Byzantine empire there is continuity in the consumption of an enzyme fermented sauce, though not as widespread, while in the West, fish sauce had become unpopular in some quarters, and scarce in terms of trade. This period of transition between what was widespread popularity and consumption in the Roman empire to irregular scarcity in the Christian West is discussed in this paper in relation to perceptions of food prohibitions.